Hematology Profile of Pregnant Women in Trimester III with Covid-19 - Ririn Handayani; Ernawati Anggareni; Nazmi Kamila (STIKes Patria Husada Blitar, 2022)
Women pregnant classified as vulnerable groups because of changes in body physiology and immune response mechanisms in their bodies. SARS-CoV-2 infection in pregnancy stimulates an increase in the expression of proinflammatory cytokines, namely IL-6, IL-12, IL-1β, dan IFNγ which can damage lung organs. The purpose of this study was to look at the hematological profile of pregnant women with COVID-19, especially in the third trimester as an effort to detect the severity of the infection experienced by the mother. This study was a quantitative descriptive study with a retrospective design using secondary data from medical records. This study was carried out at dr. Soebandi Hospital Jember, medical record data were taken from January to December 2021. The subjects of study were pregnant women in the third trimester with COVID-19. The sampling technique total sampling. Method of analysis in this study used a frequency distribution. Results of the study showed that 100% of pregnant women with COVID-19 had symptoms of cough, runny nose, fever and shortness of breath. Results of the mother's hematological examination showed an increase in leukocytes (48%) and a decrease in lymphocytes (92%), most of the mothers had anemia (76%), there was a decrease in platelets (8%) and an increase in platelets (20%). In conclusion, they had the same symptoms as patients in general, including cough, runny nose, fever to shortness of breath, an increase in leukocytes and a decrease in lymphocytes, most of the mothers also experience anemia and changes to abnormal maternal platelets occur.